ANALYSIS OF THERMAL STATE OF TRACTION BRUSHLESS PERMANENT MAGNET MOTOR FOR MINE ELECTRIC LOCOMOTIVE - A. V. Matyuschenko (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. The study was conducted to analyze thermal state of the traction permanent magnet synchronous motor for mine electric battery locomotive when operating in continuous and short-time duty modes. These operating modes are selected for study, as they are typical for mine electric locomotives. Methodology. Thermal calculation was performed by means of FEM in three-dimensional formulation of problem using Jmag-Designer. Results. The modeling results of thermal state of the PMSM in continuous and short-time duty operation modes showed good agreement with experimental results. The results showed that the temperature of PM is higher than temperature of the stator winding in continuous operation mode. It was found that PM temperature might reach excessive values because of the high presence of eddy current losses in neodymium PM. Therefore, special attention in the design and testing of PMSM should be paid to the temperature of PM in various operation modes. Practical value. It was recommended to use high temperature permanent magnets in traction PMSM to avoid demagnetization of PM and performance degradation.